Analysis Of Politiety Principles In Zenius Indonesian Learning Videos In The Playlist “It's CLEAR!” - Leni Septiani; Della Marisa Indriyani; Saiska Dwi Arimbi; Angel Eliezer Wijaya; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Yerry Mijianti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Language politeness is something important in the communication process. The principle of politeness is everything related to the rules in speech acts. In this case, the principle of politeness has a very important role so that communication goes well and can be accepted by the speech partner so that both speakers are able to understand the topic being discussed. The analysis of language politeness in this study was in the form of five videos, each of which lasted approximately ten minutes. The purpose of this research is to find out and describe the principles of politeness in the language used in the “Jelas Deh!” program. The method used is through a theoretical approach in the form of thimble studies in the principle of politeness in language. Researchers used data collection techniques, the data collected in the form of oral speech as the object of research in a conversation. Then proceed by using the listening technique and note-taking technique. In this analysis, ten kinds of thimbles were found, including generosity, wisdom, appreciation, simplicity, apology, forgiveness, consensus, opinion, sympathy, and feelings. In this analysis, it was found that a total of 76 data on the use of thimbles were complied with.